Answer:
no solution
Step-by-step explanation:
y = -2x + 3
6x + 3y = -3
the substitution method means you plug one equation into the next, because the first equation gives us a solution for y we can go ahead and plug that into y of the second equation
6x + 3(-2x + 3) = -3
6x - 6x + 9 = -3
9 = -3
which is false meaning that there are no solutions and the lines don't touch at any point
Answer:
$3142.86
Step-by-step explanation:
3300 --> 105%
x --> 100%
criss cross method
x=330000/105
x=3142.86
Hello from MrBillDoesMath!
Answer:
x = ( -9 + sqrt(33) ) /4
and
x = ( -9 - sqrt(33) ) /4
Discussion:
Using the quadratic formula with a = 2, b = 9 and c = 6 gives
x = ( -b +\- sqrt(b^2-4ac) )/2a
x = ( -9 +\- sqrt(9^2 - 4*2*6)) / (2*2) =>
x = ( -9 +\- sqrt (81- 48)) / 4 =>
x = ( -9 +\- sqrt(33) ) /4
Thank you,
MrB